Improving knowledge about breast cancer and breast self examination in female Nigerian adolescents using peer education: a pre-post interventional study - Ayebo E. Sadoh; Clement Osime; Damian U. Nwaneri; Bamidele C. Ogboghodo; Charles O. Eregie; Osawaru Oviawe (BMC, 2021)
Abstract Background Prevention of BC of which the cornerstone is creating awareness and early detection is important in adolescents and young women because of their worse outcomes. Early detection strategies such as mammography are currently beyond the reach of most women in sub-Saharan Africa.. Lack of awareness and late presentation contribute to the poor outcomes. Awareness creation among adolescents may result in modification of some risk factors for BC with adoption of healthy life styles including accessing early detection activities. This study determined the effect of peer education as a strategy to create awareness on BC and breast self examination (BSE) among in-school female adolescents in Benin City. Methods This was a pre-post interventional study carried out in October -December 2016 on female students of four secondary schools in Benin City. Pre-peer training, using a pre-tested self-administered questionnaire, knowledge about BC and BSE was assessed in about 30% of each school population. This was followed by training of 124 students selected from the schools (one student per class) as peer trainers. The peer trainers provided training on BC and BSE (the intervention) for their classmates. Within two weeks of peer training knowledge about BC and BSE was reassessed in 30% of each school population. Selection of students for assessment pre and post intervention was by systematic sampling. Correct knowledge was scored and presented as percentages. Chi square test, student t test and ANOVA were used to assess associations and test differences with level of significance set at p < 0.05. Results There were 1337 and 1201 students who responded to the pre and post-training questionnaires respectively. The mean BC knowledge score (20.61 ± 13.4) prior to training was low and it statistically significantly improved to 55.93 ± 10.86 following training p < 0.0001 Following peer training, statistically significant improvement (p 0.037- < 0.001) occurred in most knowledge domains apart from symptomatology. Pre-peer training 906(67.8%) students knew about BSE but only 67(4.8%). Significantly more students 1134(94.7%) knew about BSE following peer training. Conclusions Peer education strategy can be used to improve BC and BSE knowledge in adolescents. This strategy is low cost and could be very useful in low resource settings.